What science is about – development of the scientific understanding of secondary school students. Issue 2 (3rd April 2017) - Cincera, Jan; Medek, Michal; Cincera, Pavel; Lupac, Miroslav; Tichá, Irena
Abstract: Background: Development of scientific understanding of secondary school students is considered to be one of the goals of environmental education. However, it is not quite clear what instructional strategies and what other factors contribute to the effectiveness of environmental education programs promoting this goal. Purpose: The aim was to analyze if an applied instructional strategy applied on an outdoor environmental education program was successful in developing the students' scientific understanding, their interest in studying science at university, and if the students' scientific understanding is influenced by their gender or intention to study science at university. Program description: The investigated program was 3–5 days long and it was based on principles of inquiry-based learning approach applied in outdoor setting of an environmental education center. Sample: For the analysis, data from 83 students (60 girls, 23 boys) of three grammar schools who participated in the program (mean age of 16.45 years), were collected. The control group consisted of 93 students (59 girls and 34 boys), with a mean age of 17.5 years. Design and methods: The research applied a quasi-experimental non-equivalent control group design when both group received the same instruments in the same time span. The instrument consisted of three parts: 1-item Science and Engineering Indicator, 1 Likert-type item for assessing students' intention to study science, and a problem-based task for assessing students' understanding of the procedure of scientific inquiry. Results: The program seemed to positively affect students' understanding of scientific principles and procedures; however, no effect on their intention to study science at university was found. Conclusions: The evaluated strategy which consisted of elements such as the application of mobile technology, balancing between teacher- and student-directed approaches, and emotion-based activities was proven effective for developing students' scientific understanding. However, in order to increase students' intention to study science, a different or a better developed strategy is needed.